The CAF1-NOT complex of trypanosomes - Erben, Esteban; Chakraborty, Chaitali; Clayton, Christine (Frontiers in Genetics, 2014)
In African trypanosomes, there is no control of transcription initiation by RNA polymerase II at the level of individual protein-coding genes. Transcription is polycistronic, and individual mRNAs are excised by trans splicing and polyadenylation. As a consequence, trypanosomes are uniquely reliant on post-transcriptional mechanisms for control of gene expression. Rates of mRNA decay vary over up to two orders of magnitude, making these organisms an excellent model system for the study of mRNA degradation processes. The trypanosome CAF1-NOT complex is simpler than that of other organisms, with no CCR4 or NOT4 homologue: it consists of CAF1, NOT1, NOT2, NOT5 NOT9, NOT10 and NOT11. It is important for the initiation of degradation of most, although not all, mRNAs. There is no homologue of NOT4, and Tho and TREX complexes are absent. Functions of the trypanosome NOT complex are therefore likely to be restricted mainly to deadenylation. Mechanisms that cause the NOT complex to deadenylate some mRNAs faster than others must exist, but have not yet been described.